STABILITAS AKTIVITAS ALT SERUM, PLASMA HEPARIN - Chitra Adzka Nabila Chindara; Nani Kurnaeni; Betty Nurhayati; Sonny Feisal Rinaldi (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2019)
Most errors in clinical laboratory examinations, namely in the pre-analytic stage can occur when handling samples. One clinical laboratory examination is examination of ALT activity. Based on interviews, specimens are usually stored in the laboratory at 2-8oC before being destroyed with different times per laboratory. Specimens that can be used to examine ALT activity are serum, heparinised plasma, and EDTA plasma. This study aims to look at the stability of serum and plasma samples with 3 different types of samples against ALT parameters. The number of samples used was 2400 µL for each. The methods of this study were serum samples, heparinised plasma, and EDTA plasma that were directly examined and postponed for a total of 15 days stored at refrigerator temperature. Examination of ALT activity using the IFCC kinetic method. The data obtained were analyzed using the GLM Repeated Measure test, the results were not statistically different in serum samples between direct examined and delayed (p >0.050). In heparinised plasma and EDTA plasma samples there were statistical differences between direct examined and delayed (p <0.050) on day 7 and day 9 respectively, there were also clinical differences in heparinised plasma and EDTA plasma between direct examined and delayed respectively on day 9 (25.2%) and day 15 (22.3%). From these results it can be concluded that ALT in serum is stable for up to 15 days, in heparinised plasma is stable up to 7 days, and EDTA plasma is stable for up to 13 days at storage temperature 2-8oC.